2008
DOI: 10.1097/pas.0b013e318160736a
|View full text |Cite
|
Sign up to set email alerts
|

Ossifying Fibromyxoid Tumor of Soft Parts—A Clinicopathologic and Immunohistochemical Study of 104 Cases With Long-term Follow-up and a Critical Review of the Literature

Abstract: Ossifying fibromyxoid tumor (OFT) is a unique soft tissue tumor of uncertain histogenesis. The majority of reported cases (approximately 220) have pursued a benign clinical course. However, recent literature has emphasized the existence of morphologically atypical and clinically malignant examples of this tumor and proposed guidelines for assessment of biologic potential. In the present study, we evaluated 104 cases of OFT from the Armed Forces Institute of Pathology, accessioned between the years 1970 and 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
200
1
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(212 citation statements)
references
References 43 publications
(50 reference statements)
5
200
1
6
Order By: Relevance
“…These tumors show a distinctive lobulation and in most cases a bone shell is evident. [27][28][29] Metaplastic bone formation known in soft tissue myoepithelial tumors is not described in skin lesions. [1][2][3][4][5][6][7][8] Moreover, the intratumoral cytological and architectural heterogeneity of myoepithelial tumors is not a feature of ossifying fibromyxoid tumors in which uniform round to oval cells in cords and nests set in a myxohyaline stroma.…”
Section: Ewsr1 In Cutaneous Myoepitheliomamentioning
confidence: 99%
See 1 more Smart Citation
“…These tumors show a distinctive lobulation and in most cases a bone shell is evident. [27][28][29] Metaplastic bone formation known in soft tissue myoepithelial tumors is not described in skin lesions. [1][2][3][4][5][6][7][8] Moreover, the intratumoral cytological and architectural heterogeneity of myoepithelial tumors is not a feature of ossifying fibromyxoid tumors in which uniform round to oval cells in cords and nests set in a myxohyaline stroma.…”
Section: Ewsr1 In Cutaneous Myoepitheliomamentioning
confidence: 99%
“…4,6,7 Immunohistochemical stains in this setting are of limited value because of the overlap with positivity for S100, GFAP, myogenic markers and rarely also keratins. 4,6,7,[27][28][29] Even though in a small number of cases investigated, ossifying fibromyxoid tumors show no abnormality in EWSR1. 10 In summary, our study demonstrated that cutaneous myoepithelial tumors harbor EWSR1 rearrangement in a subset of cases, and therefore are genetically related to soft tissue and bone myoepithelial tumors and the visceral counterpart in the lung.…”
Section: Ewsr1 In Cutaneous Myoepitheliomamentioning
confidence: 99%
“…These different X-ray appearances of the fibromyxomas pose a diagnostic problem with ameloblastomas, giant cell tumors, and intraosseous hemangiomas, as described in the literature; hence, a histopathological examination that provides confirmation of diagnosis is required [13,15]. The presence of calcifications found in the histopathological examination was also observed by Miettinen et al [12]. These calcifications are specific characteristics of the fibromyxomas and are essential for the differential diagnosis [11,16].…”
Section: Discussionmentioning
confidence: 81%
“…Studies on fibromyxoma of the maxilla are numerous, but those reporting the details of relationships with the surrounding soft tissues are rare [11,12]. This localization to the gingiva could be explained by the ectomesenchyme from the embryonic remnants of the periodontal ligament.…”
Section: Discussionmentioning
confidence: 99%
“…While epithelioid schwannoma can be described as a benign nerve sheath tumour of peripheral nerves, OFMT is considered to be a intermediate (borderline) malignant soft tissue tumour. There are differing opinions regarding the origin of the tumour (Kindblom et al, 1998;Miettinen et al, 2008).…”
Section: Introductionmentioning
confidence: 99%